2013
DOI: 10.1111/vcp.12074
|View full text |Cite
|
Sign up to set email alerts
|

Skunk musk causes methemoglobin and Heinz body formation in vitro

Abstract: In vitro, skunk musk causes Heinz body and methemoglobin formation in canine, feline, and Red Panda RBC, supporting the clinical association between Heinz body hemolytic anemia and skunk spray exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…In this case series, 2 dogs (Dog 5 and Dog 11) had diabetes mellitus, and 1 (Dog 3) had diabetic ketoacidosis. Studies have shown that diabetic ketoacidosis can cause oxidative damage to erythrocytes in cats and dogs ( 11 , 12 , 20 , 21 ). Additionally, some dogs in the present case series had inflammatory diseases (pancreatitis [Dog 3, Dog 4, and Dog 11] and pyometra [Dog 10]), which could contribute to oxidative damage, and 1 dog (Dog 4) had lymphoma, which could also cause oxidative damage ( 20 , 21 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case series, 2 dogs (Dog 5 and Dog 11) had diabetes mellitus, and 1 (Dog 3) had diabetic ketoacidosis. Studies have shown that diabetic ketoacidosis can cause oxidative damage to erythrocytes in cats and dogs ( 11 , 12 , 20 , 21 ). Additionally, some dogs in the present case series had inflammatory diseases (pancreatitis [Dog 3, Dog 4, and Dog 11] and pyometra [Dog 10]), which could contribute to oxidative damage, and 1 dog (Dog 4) had lymphoma, which could also cause oxidative damage ( 20 , 21 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that diabetic ketoacidosis can cause oxidative damage to erythrocytes in cats and dogs ( 11 , 12 , 20 , 21 ). Additionally, some dogs in the present case series had inflammatory diseases (pancreatitis [Dog 3, Dog 4, and Dog 11] and pyometra [Dog 10]), which could contribute to oxidative damage, and 1 dog (Dog 4) had lymphoma, which could also cause oxidative damage ( 20 , 21 , 31 ). Since there was no correlation between the number of HBs and the dose of metamizole and because many dogs in this case series had multiple diseases/problems, the oxidative damage to erythrocytes could have been multifactorial and not only related to oxidative damage secondary to metamizole administration, at least in some dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N. nasua is a member of the Family Procyonidae, Superfamily Canoidea, and Order Carnivora; therefore, the ferret and dog represent its closest domestic relatives . Heinz body hemolytic anemia has previously been described in dogs, cats, horses, ruminants, and a ferret, and has rarely been reported in captive or free‐ranging wild animals, including Atlantic puffins, common marmosets, cotton‐top tamarins, herring gulls, koalas, murres, a red panda, and a river otter . Heinz bodies have been described in the erythrocytes of healthy cats and several wild mammals but not in healthy coatis .…”
Section: Discussionmentioning
confidence: 99%
“…Methemoglobinemia in small animals has been documented to result from a variety of causes including congenital deficiencies such as methemoglobin reductase deficiency (cytochrome b5R deficiency),1,2 acetaminophen ingestion,3 topical benzocaine products,4 skunk musk,5 hydroxycarbamide,6 phenazopyridine,7 and nitrates/nitrites 8. Hemoglobin, as an oxygen-binding molecule, requires iron in the ferrous state for oxygen binding to occur.…”
Section: Introductionmentioning
confidence: 99%